2.1 μm InGaSb quantum well lasers exhibiting the maximum conversion efficiency of 27.5% with digitally grown AlGaAsSb barriers and gradient layers. (June 2019) - Xie, Shengwen; Yang, Chengao; Huang, ShuShan; Yuan, Ye; Zhang, Yi; Shang, Jinming; Cai, Chenyuan; Zhang, Yu; Xu, Yingqiang; Ni, Haiqiao; Niu, Zhichuan
Abstract: The 2.1-μm-wavelength InGaSb/AlGaAsSb/GaSb double quantum well lasers, exhibiting a high performance with the peak output power of 1.62 W and the maximum conversion efficiency of 27.5%, had been grown by molecular-beam-epitaxy (MBE). Digitally grown Alx Ga1-x AsSb barriers and grading layers were employed in the devices to increase the valence-band offset and to improve the simplicity and controllability of MBE growth. The quaternary digital alloys were grown with short-period superlattices (SPS) of AlSb, AlAs and GaSb and varieties of growth conditions such as growth temperature, interface control and growth rate were considered to get the high-quality crystal films. The digitally grown film was parametrically characterized by atomic force microscopy, high resolution X-ray and transmission electron microscope, showing a smooth surface, clear satellite peaks and clear growth cross sections, respectively. Besides the good power performance of the devices, a low threshold current density of 60 A/cm 2 was also achieved and the calculated differential resistance was 0.17 Ω. Highlights: The growth conditions of AlGaAsSb digital alloys by MBE were fully discussed. The AlGaAsSb digital alloys were grown with AlSb, AlAs, GaSb binary materials with interface control. The growth methods of the digitally grown AlGaAsSb grading layers were analyzed in detail. The 2.1-μm-wavelength InGaSb/AlGaAsSb/GaSb laser devices were grown with the AlGaAsSb digital alloys. The laser devices exhibit a peak output power of 1.62 W and the maximum conversion efficiency of 27.5%.